A double-blind, randomized controlled trial to evaluate the safety and immunogenicity of an intranasally administered trivalent inactivated influenza vaccine with the adjuvant LTh(αK): A phase II study. Issue 5 (29th January 2020) - Pan, Sung-Ching; Hsu, Wei-Ting; Lee, Wen-Sen; Wang, Ning-Chi; Chen, Tzeng-Ji; Liu, Ming-Che; Pai, Hui-Chen; Hsu, Yu-Shen; Chang, Mingi; Hsieh, Szu-Min
Abstract: Background: Intranasal influenza vaccines may provide protective efficacy by inducing both systemic antibodies and local secretory IgA. Live attenuated intranasal vaccines are not feasible for high-risk groups. A previously constructed inactivated vaccine with adjuvant revealed an association with neurological events in some studies. In this phase II trial, we aimed to evaluate the safety and immunogenicity of an intranasal influenza vaccine with a novel adjuvant, heat-labile enterotoxin (LT)-derived from E. coli (LTh(αK)). Methods: This study is a multicenter, randomized controlled, double-blind, phase II trial of an intranasal influenza vaccine containing 22.5 μg of the hemagglutinin (HA) antigen of three influenza strains in combination with 2 different LTh(αK) adjuvant doses (group 1: 30 μg; group 2: 45 μg) in subjects 20–70 years old. The control vaccine was 22.5 μg of influenza HA antigen alone (group 3). The vaccine was intranasally administered on days 1 and 8. Serum anti-HA antibody and nasal secretory IgA were measured, and adverse events (AEs) were recorded prevaccination and 29 (±2) days postvaccination. Results: Of 354 participants randomized in the study, 340 received two vaccine doses. AEs were mostly mild, and there was no discontinuation related to the vaccine. Only a higher frequency of diarrhea after the first dose was noted among group 2 (11.5%) than among group 3 (2.8%), and there was no significant difference after the second dose. The three groups had comparable serum anti-HA antibody immunogenicity. However, the adjuvanted vaccines induced greater mucosal IgA antibody production than the control vaccine. In a subgroup analysis, group 1 participants achieved adequate immunogenicity among both 20- to 60- and 61- to 70-year-old participants. Conclusion: The intranasal influenza vaccine adjuvanted with LTh(αK) is generally safe and could provide systemic and local antibody responses. Adjuvanted vaccines were significantly more immunogenic than the nonadjuvanted control vaccine in mucosal immunity. ClinicalTrials.gov Identifier : NCT03784885.